Coerced addiction treatment: Client perspectives and the implications of their neglect - Urbanoski Karen A (BMC, 2010)
Abstract Recent work has criticized the evidence base for the effectiveness of addiction treatment under social controls and coercion, suggesting that the development of sound policies and treatment practices has been hampered by numerous limitations of the research conducted to date. Implicit assumptions of the effectiveness of coerced treatment are evident in the organization and evolution of treatment, legal, and social service systems, as well as in related legislative practices. This review builds upon previous work by focusing in greater detail on the potential value of incorporating client perspectives on coercion and the implications for interpreting and applying existing research findings. Reviewing the existing empirical and theoretical literature, a case is made for greater accuracy in representing coercive experiences and events in research, so as to better align the measured concepts with actual processes of treatment entry and admission. Attention is given to studies of the effectiveness of treatment under social controls or pressures, the connections to coercion and decision-making, and theoretical perspectives on motivation and behaviour change, including Self-Determination Theory in particular. This synthesis of the available research on coerced addiction treatment suggests that it remains largely unclear to what extent many of the commonly employed methods for getting people into treatment may be detrimental to the treatment process and longer-term outcomes. The impact of coercion upon individual clients, treatment systems, and population health has not been adequately dealt with by addiction researchers to date.